Leaf litter decomposition rates: influence of successional age, topography and microenvironment on six dominant tree species in a tropical dry forest - Morffi-Mestre, Hernán; Ángeles-Pérez, Gregorio; Powers, Jennifer S.; Andrade, José Luis; Feldman, Richard Evan; May-Pat, Filogonio; Chi-May, Francisco; Dupuy-Rada, Juan Manuel (Frontiers in Forests and Global Change, 2023)
Litter decomposition is a central process in forest ecosystems because of its role in carbon and nutrient cycling and maintaining soil fertility. Decomposition is affected by plant traits, soil and microenvironmental conditions, topography, and vegetation structure, which varies with successional age. However, it is unclear how all these factors affect leaf decomposition of dominant tree species in tropical dry forests (TDFs). The objective of this study was to compare the decomposition rates of six dominant tree species: three legumes (Caesalpinia gaumeri, Lysiloma latisiliquum, Piscidia piscipula) and three non-legumes (Bursera simaruba, Gymnopodium floribundum, Neomillspaughia emarginata) in five successional age categories (8–10, 15–22, 23–30, 65–84, > 85 years-old) and two topographic conditions (flat and sloping sites) in a TDF, and to analyze the association with leaf traits (toughness, N, C and total phenols content) soil properties (bulk density, organic carbon, pH, clay), microenvironmental (litter and soil moisture, leaf area index), and vegetation variables (basal area, aboveground biomass, tree diameter, tree height). Litterbags were placed in 30–400 m2 circular plots distributed in forests of the Yucatan, Mexico, and collected on six occasions spread over 230 days (540 samples per species). L. latisiliquum and C. gaumeri had the highest decomposition rates (as well as leaf nitrogen concentration and the lowest leaf toughness). Conversely, G. floribundum had the lowest decay rate. Decomposition rate reached high values at intermediate successional ages, suggesting that soil fertility recovers rapidly after disturbance, although only L. latisiliquum showed significant differences among stand age categories. Decomposition rate was consistently higher at flat sites than on slopes but the difference was significant only for L. latisiliquum. The soil, vegetation structure and microenvironmental variables that contributed most to explaining variation in decay rates varied among species. Decomposition tended to increase with soil moisture and clay content, and to decrease with soil organic carbon and pH suggesting susceptibility to climate change and soil erosion, particularly in sloping areas. Our results highlight the importance of analyzing species-specific responses, especially for dominant species, which likely contribute most to leaf litter decomposition, and to consider key ecological factors that influence this key process.